2019
DOI: 10.1200/jco.2019.37.15_suppl.9107
|View full text |Cite
|
Sign up to set email alerts
|

Fast-progression (FP), hyper-progression (HPD) and early deaths (ED) in advanced non-small cell lung cancer (NSCLC) patients (pts) upon PD-(L)-1 blockade (IO).

Abstract: 9107 Background: HPD was described in 13.8% of NSCLC pts upon single-agent IO and correlated with high metastatic burden and poor prognosis. Other progression (PD) patterns as FP and ED within 12 weeks have been reported respectively in 4.7% and 5.6% of atezolizumab treated NSCLC pts. Whether FP/ED and HPD are different or overlapping patterns is currently unknown. Methods: We analyzed FP, ED and HPD in a multicentric (8 centers) retrospective cohort of IO treated NSCLC pts (11/2012-04/2017). Eligibility crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 0 publications
1
29
1
Order By: Relevance
“…Ferrara et al (8) reported that patients who developed HPD within the first 6 weeks after treatment with a PD-1/PD-L1 inhibitor had an mOS of 3.4 months (n=23; 95% CI: 2.8-7.5 months). The mOS of FP patients was significantly shorter than that of HPD patients (0.7 vs. 1.6 months, P=0.02) (14). The mOS in our study appeared to be longer than those reported in previous studies, which may be due to our small sample size and the fact that a higher proportion of patients in our study received immunotherapy as a first-or second-line treatment.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Ferrara et al (8) reported that patients who developed HPD within the first 6 weeks after treatment with a PD-1/PD-L1 inhibitor had an mOS of 3.4 months (n=23; 95% CI: 2.8-7.5 months). The mOS of FP patients was significantly shorter than that of HPD patients (0.7 vs. 1.6 months, P=0.02) (14). The mOS in our study appeared to be longer than those reported in previous studies, which may be due to our small sample size and the fact that a higher proportion of patients in our study received immunotherapy as a first-or second-line treatment.…”
Section: Discussioncontrasting
confidence: 80%
“…Ferrara et al (14) reported that 6/6 FP patients and 21/46 ED patients were also classified as HPD based on TGR analysis. In our study, 3/6 FP patients and 2/3 ED patients were also classified as HPD, and 1 patient qualified for all 3 definitions (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A different clinical entity described is fast progression (FP), which is a progression within the first radiologic evaluation or no later than 12 weeks but not classifiable as HPD criteria [ 59 ]. According to some small evidence on the biological mechanisms, HPD is associated with a disimmunity, while FP is associated with primary resistance to immunotherapy [ 28 , 55 , 59 ].…”
Section: Systemic Progressionmentioning
confidence: 99%